Pelatihan Pembuatan Sabun Mandi Eco Enzim Di Kelompok Ibu-Ibu Dawis - Darsini, Darsini; Suprapto, Suprapto; Ahya, Rahmatul; Sri L, Mathilda (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
The problem faced by mothers, especially Dawis Melati 2 RT 07 RW 03 Jombor Bendosari Sukoharjo, is the use of conventional bath soap which contains dangerous chemicals and is not environmentally friendly. The proposed solution is to provide training to groups of mothers in Dawis to make eco enzyme soap. Competitive Community Service in the Field of Science (PMKBI) aims to empower groups of mothers, especially housewives. The method used is in 2 stages, the first is an introduction to the benefits of eco-enzymes and an introduction to the ingredients used to make soap. The second stage is training in the process of making bath soap using environmentally friendly eco-enzyme ingredients. Apart from that, education was also provided about the dangers of chemicals in conventional soap. The number of participants who attended the training was 17 women. Before the training was carried out, a pre-test was given and an average score of 51.57% was obtained and the post-test score after the training was 83.53%, so there was an increase in knowledge of 32%, so knowledge mothers about eco-enzyme bath soap and how to make it can be understood and known well. Based on the calculation of the value of the rupiah, if calculated from 1 month's expenditure, an average of 4 pieces cost Rp. 25,000, the cost of making eco-enzum soap per production could be 8 pieces with a production cost of Rp. 50,000, so you can save Rp. 25,000,-. each month.